Genetic identification of a crayfish (Astacus) species at the northern edge of their distribution area (Solovetsky Islands, White Sea). (April 2016) - Borovikova, Elena A.; Alekseeva, Jaroslava A.; Bagirov, Nizami E.; Makhrov, Alexander A.; Popov, Igor Yu.
Highlights: Genetic analysis showed that the crayfish belonged to the species Astacus leptodactylus. Crayfish have been intentionally introduced to the Solovetsky Islands. Further spread of the narrow-clawed crayfish across northern Europe is probable.